2020
DOI: 10.3390/sym12091467
|View full text |Cite
|
Sign up to set email alerts
|

Fluid-Structure Interaction of Wind Turbine Blade Using Four Different Materials: Numerical Investigation

Abstract: The interaction of a flexible system with a moving fluid gives rise to a wide variety of physical phenomena with applications in various engineering fields, such as aircraft wing stability, arterial blood progression, high structure reaction to winds, and turbine blade vibration. Both the structure and fluid need to be modeled to understand these physical phenomena. However, in line with the overall theme of this strength, the focus here is to investigate wind turbine aerodynamic and structural analysis by com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 35 publications
0
17
0
Order By: Relevance
“…The SST k-ω model is one of the popular two-equation RANS models; it accounts for the transport of the turbulent shear stress and provides highly exact predictions of the onset and the amount of flow separation under adverse pressure gradients. The detailed equations of the SST k-ω model are presented in [26].…”
Section: Turbulence Modelmentioning
confidence: 99%
“…The SST k-ω model is one of the popular two-equation RANS models; it accounts for the transport of the turbulent shear stress and provides highly exact predictions of the onset and the amount of flow separation under adverse pressure gradients. The detailed equations of the SST k-ω model are presented in [26].…”
Section: Turbulence Modelmentioning
confidence: 99%
“…Finally, by combining Equations (7)- (12) and Equations (13) and (14), the following equations are obtained as:…”
Section: Analytical Modelmentioning
confidence: 99%
“…Therefore, wind loads should not excite the vibration modes of the blades to avoid excessive vibration displacements [11]. Briefly, the structural dynamic and aeroelastic behaviour of wind turbines should be considered during their design process [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…The influence of the generator was negligible at low wind speeds, but in any case, the protective cover was useful to the loss caused by the erosion of the airfoil. Roul [23] used finite element analysis (FEA) methods to study the aerodynamics and structural analysis of wind turbines, and found that the pitch angle had a prominent influence on the output of wind turbines, which could provide a new idea for turbine blade erosion protection.…”
Section: Introductionmentioning
confidence: 99%